Applicability of augmented reality in orthopedic surgery - A systematic review - Jud, Lukas; Fotouhi, Javad; Andronic, Octavian; Aichmair, Alexander; Osgood, Greg; Navab, Nassir; Farshad, Mazda (BMC Musculoskeletal Disorders, 2020)
Background: Computer-assisted solutions are changing surgical practice continuously. One of the most disruptive technologies among the computer-integrated surgical techniques is Augmented Reality (AR). While Augmented Reality is increasingly used in several medical specialties, its potential benefit in orthopedic surgery is not yet clear. The purpose of this article is to provide a systematic review of the current state of knowledge and the applicability of AR in orthopedic surgery. Methods: A systematic review of the current literature was performed to find the state of knowledge and applicability of AR in Orthopedic surgery. A systematic search of the following three databases was performed: "PubMed", "Cochrane Library" and "Web of Science". The systematic review followed the Preferred Reporting Items on Systematic Reviews and Meta-analysis (PRISMA) guidelines and it has been published and registered in the international prospective register of systematic reviews (PROSPERO). Results: 31 studies and reports are included and classified into the following categories: Instrument / Implant Placement, Osteotomies, Tumor Surgery, Trauma, and Surgical Training and Education. Quality assessment could be performed in 18 studies. Among the clinical studies, there were six case series with an average score of 90% and one case report, which scored 81% according to the Joanna Briggs Institute Critical Appraisal Checklist (JBI CAC). The 11 cadaveric studies scored 81% according to the QUACS scale (Quality Appraisal for Cadaveric Studies). Conclusion: This manuscript provides 1) a summary of the current state of knowledge and research of Augmented Reality in orthopedic surgery presented in the literature, and 2) a discussion by the authors presenting the key remarks required for seamless integration of Augmented Reality in the future surgical practice. Trial registration: PROSPERO registration number: CRD42019128569.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented reality; Image overlay; Orthopaedic surgery; Trauma surgery